Differentiating Medical Malpractice From Medical Complications - Vojković, Hrvoje (Medicine, Law & Society, 2019)
Determining the notion of medical complications leads to differentiating in particular complications that are the unwanted result of a medical procedure. In particular, the factual and medical cause is to be sought in the nature of the damage and the circumstances of its onset through no fault of the physician, from those complications that are the undesired consequence of unprofessional medical care. In the latter case law theory and practice recognizes a situation that is standing in a causal relationship with legally relevant damages and which makes the medical practitioner civilly liable for harmful consequences. Therefore, complications in medical treatment procedures are a harmful event occurring in the medical treatment of a patient which is caused by the undesired and unavoidable course of illness/injury or the patient’s overall state of health, despite the fact that the medical treatment was performed completely lege artis, and in accordance with moral and ethical principles of the healthcare profession and standards in modern medical science.